Wave-absorbing prepreg with high carbon-series wave-absorbing agent content and preparation method of wave-absorbing prepreg
By dividing the carbon-based absorbent into two parts and using the hot melt impregnation method to prepare the absorbent prepreg with high carbon-based absorbent content, the problem of difficulty in improving the carbon-based absorbent content in the prior art is solved, and the absorption performance is improved and the material is lightened.
Patent Information
- Application Number
- CN202411811443.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-12-10
AI Technical Summary
The prior art is difficult to increase the content of carbon-based absorbents in the prepreg, making it difficult to compare the absorbing performance with the iron-based absorbing materials.
By dividing the carbon-based absorbent into two parts, a part of the high-concentration slurry is applied to the fiber cloth, and a three-dimensional "sandwich" structure is formed through the suture technology, and a small part of the carbon-based absorbent is added to the resin matrix, and a high-carbon-based absorbent content is prepared by hot melt impregnation method.
The controllable range of the amount of the absorbent absorbent is significantly improved, the absorbent performance is improved, the loss of the absorbent agent is reduced, and while maintaining the processing performance, the preparation of prepregs with high carbon-based absorbent content is realized.
Smart Images

Figure CN119502535A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of microwave absorbing prepregs, and in particular to a microwave absorbing prepreg with a high carbon-based microwave absorbing agent content and a preparation method thereof. Background Art
[0002] With the development of aerospace technology and electronic information technology, high-speed aircraft, low-altitude drones, ships, and special vehicles have all put forward the demand for stealth functions to improve the survivability of military equipment in complex battlefield environments, thereby adapting to the development trend of modern electronic information warfare. Therefore, absorbing materials are becoming a hot topic in the current materials field.
[0003] Absorbing materials refer to materials that achieve "invisibility" by absorbing and attenuating incident electromagnetic waves and converting them into heat dissipation or interference destructiveness. The absorbing ability of absorbing materials mainly depends on the absorbing medium, that is, the absorption efficiency of the absorber. According to the loss mechanism, absorbers can be divided into magnetic loss absorbers, resistance loss absorbers and dielectric loss absorbers. Traditional iron powder, ferroalloy powder, ferrite and carbonyl iron powder mainly absorb and attenuate electromagnetic waves through hysteresis loss, which are typical magnetic loss absorbers. They have the advantages of strong absorption efficiency and low price, but also have disadvantages such as high density, poor thermal stability and poor chemical resistance. Carbon absorbers such as carbon black, graphene, carbon nanotubes, chopped carbon fibers, silicon carbide, etc. mainly absorb and dissipate electromagnetic waves through eddy current loss, which are typical resistance absorbers. They have the advantages of low density, wide absorption bandwidth, good temperature resistance, good corrosion resistance and good oxidation resistance.
[0004] Compared with iron-based absorbers, carbon-based absorbers have advantages such as low density, low weight gain, and good chemical resistance, and are more suitable for the field of aircraft; however, carbon-based absorbers have high oil absorption, large specific surface area, and high surface energy, which leads to a small amount of them in the resin formulation system. For example, it has been reported that the amount of carbon-based absorbers added to the formula is 40% by volume, but its mass fraction is actually <4 wt%; experiments show that in a solvent-free resin formulation system, the amount of carbon-based absorbers added is difficult to exceed 5 wt%, while maintaining good processability; when the content of carbon-based absorbers in the resin system is too high, the system viscosity increases significantly, the thixotropy is obvious, the fluidity is poor, the coating processability is poor, and the molding crosslinking density decreases and the mechanical properties decrease. In contrast, the amount of iron-based absorbers added can even exceed 70 wt% while maintaining good processability; thus, it is difficult to compare the absorbing performance of carbon-based absorbers with that of iron-based absorbers.
[0005] How to increase the content of the microwave absorber in the prepreg and prepare a microwave absorbing prepreg with a high carbon-based microwave absorber content, thereby effectively improving the microwave absorbing performance, is a problem to be solved by the present invention. Summary of the invention
[0006] In order to solve the above technical problems, the purpose of the present invention is to provide an absorbing prepreg with a high carbon-based absorber content and a preparation method thereof, which method significantly improves the carbon-based absorber content and the absorbing efficiency in the absorbing prepreg, and at the same time, the layer thickness also has obvious operational space, thereby greatly broadening the application scope of the absorbing prepreg and meeting the needs of diversified products.
[0007] The technical solution of the present invention to solve the above technical problem is as follows: a method for preparing a microwave absorbing prepreg with a high carbon-based microwave absorbing agent content is provided, comprising the following steps: (1) stirring and mixing a carbon absorber, a volatile solvent and an active monomer diluent, and grinding and dispersing them to obtain a glue solution I-1; (2) coating the adhesive solution I-1 obtained in step (1) onto the surface of the fiber cloth, and then drying it to form a film to obtain the fiber cloth I-2; (3) Take two layers of fiber cloth I-2 obtained in step (2), put the sides coated with glue face to face, and then reinforce them by sewing technology to obtain three-dimensional cloth I-3; (4) adding the carbon-based absorber to the resin matrix, stirring, mixing, grinding and dispersing, and obtaining a mixed resin matrix II-1; (5) The mixed resin matrix II-1 obtained in step (4) is impregnated into the three-dimensional fabric I-3 obtained in step (3) by hot melt impregnation to obtain an absorbing prepreg with a high carbon absorber content.
[0008] Furthermore, in steps (1) and (4), the carbon-based absorber is at least one of graphene, carbon nanotubes, carbon black and silicon carbide.
[0009] Among them, graphene is selected with conductivity of 1000-50000 S / m, particle size of 1-100 μm and specific surface area of 100-300 m 2 / g of reduced graphene oxide powder, further selected from a powder having a conductivity of 5000-10000 S / m, a particle size of 10-20 μm and a specific surface area of 200-250 m 2 / g of reduced graphene oxide powder; carbon nanotubes with a diameter of 5-20 nm, a length of 50-500 μm and a specific surface area of 200-400 m 2 / g of multi-walled carbon nanotubes, further selected from 10-15 nm in diameter, 50-100 μm in length, and 250-300 m in specific surface area 2 / g of multi-walled carbon nanotubes; carbon black with a resistivity of 0.1-1 Ω∙m, a particle size of 5-20 μm, and a specific surface area of 500-1000 m 2 / g of conductive carbon black, further selected from a resistivity of 0.5-0.8 Ω∙m, a particle size of 10-15 μm and a specific surface area of 600-800 m 2 / g of conductive carbon black; select the purity ≥99.9%, particle size ≤0.5 μm, density 3.21 g / cm 3 and silicon carbide with a resistivity of 0.3-0.5Ω∙m.
[0010] Furthermore, the volatile solvent is a low boiling point solvent, including but not limited to conventional solvents such as alcohols, ketones, esters, and deionized water.
[0011] Furthermore, the volatile solvent is at least one of ethanol, isopropanol, n-butanol, acetone, butanone, cyclohexanone, ethyl acetate, butyl acetate, ethyl lactate and pure water.
[0012] Furthermore, the active monomer diluent in step (1) corresponds to the resin matrix in step (4). For example, the monomer diluent of the epoxy resin system includes but is not limited to aliphatic epoxy resin monomers, such as Huntsman's GE-5, GE-8, GE-13, GE-20 and GE-22, etc.; alicyclic epoxy resin monomers, such as TTA-21 and TTA-26; the monomer diluent of the cyanate resin system, which can also be the above-mentioned epoxy resin monomers, etc.; the monomer diluent of the acrylate resin system, acrylate monomers, such as methyl (meth)acrylate, butyl (meth)acrylate, lauryl (meth)acrylate, norbornyl (meth)acrylate and hexanediol diacrylate, etc.
[0013] Furthermore, in steps (1) and (4), the powder is ground to a fineness of less than 20 μm.
[0014] Furthermore, in step (1), stirring is performed at 10-500 r / min for 20-60 min.
[0015] Furthermore, in step (1), the concentration of the carbon absorber in the glue solution I-1 is 20-60 wt %, and the concentration of the active monomer diluent is 5-20 wt %.
[0016] Furthermore, in step (2), the coating amount of the adhesive solution I-1 is 50-3000 g / m 2 .
[0017] The fiber cloth surface is one of glass fiber, quartz fiber, aramid fiber, ultra-high molecular weight polyethylene fiber and polyimide fiber. The fiber cloth surface density is 40-400 g / m 2 , further 50-200 g / m 2 .
[0018] Furthermore, in step (2), the drying temperature is 60-100°C.
[0019] Furthermore, in step (4), the concentration of the carbon-based absorber in the mixed resin matrix II-1 is 0.5-5 wt%.
[0020] Furthermore, in step (4), the resin matrix is one of epoxy resin, cyanate resin and acrylate resin. The resin matrix includes resin, curing agent and auxiliary agent.
[0021] Furthermore, in step (4), stirring is performed at 50-1000 r / min for 10-30 min.
[0022] Furthermore, in step (5), the hot melt impregnation method comprises: mixing the mixed resin matrix II-1 obtained in step (4) at a temperature of 50-1000 g / m 2 The mixture is evenly coated on the release paper and then covered with the three-dimensional fabric I-3 obtained in step (3). The mixture is hot-pressed and impregnated at 50-150°C to obtain an absorbing prepreg with a high carbon absorber content.
[0023] Further, the coating amount is 40-2000 g / m 2 , further 100-500 g / m 2 ; The coating temperature is 20-80°C, further 30-70°C; The coating speed is 1-10 m / min, further 2-5 m / min.
[0024] The present invention also provides a microwave absorbing prepreg with a high carbon-based microwave absorbing agent content obtained by the method for preparing the microwave absorbing prepreg with a high carbon-based microwave absorbing agent content.
[0025] The present invention has the following beneficial effects: 1. The method of the present invention divides the carbon absorber into two parts: the majority is prepared into a high-concentration slurry and first coated on the fiber cloth, so that the amount of the absorber added is no longer limited by the resin adsorption amount and processability, greatly improving the controllable range of the absorber addition amount, and the fiber cloth coated with the absorber on one side is "face to face" laminated, and then the two layers of fiber cloth are sewn together with fiber tows to form a three-dimensional "sandwich" structure, thereby increasing the interlayer force and reducing the loss of the absorber; a small amount of the carbon absorber is added to the mixed resin and used in conjunction with the resin matrix. Since the content of the absorber in the resin formula no longer has a major influence on the total amount of the absorber, the resin viscosity can be adjusted to a suitable range, which is convenient for construction.
[0026] 2. In the present invention, the adhesive solution is composed of a small amount of active monomers and a large amount of carbon absorbers. During the preparation of prepregs, the monomers can adsorb the carbon absorbers to improve their adhesion to the fiber cloth. During the hot pressing and curing process of the material, the monomers can undergo a cross-linking reaction with the curing agent or resin that penetrates the resin matrix, so that the material is cured across layers into a three-dimensional continuous whole.
[0027] 3. Carbon-based absorbers have the characteristics of low density, large specific surface area and strong oil absorption. It is difficult to add high content in the resin formulation system. However, in the method of the present invention, the content of carbon-based absorbers after the glue is dried can actually exceed 90wt%, and the total content of carbon-based absorbers in the prepreg can also reach 70wt%, so that the prepared absorbing prepreg has the advantages of light weight and high absorbing performance, and has great application value in the field of aircraft.
[0028] 4. The center of the absorbing prepreg of the present invention is an absorbing layer with a high absorbing agent content, and the outer side is an absorbing layer with a low absorbing agent content, showing a gradient absorbing effect. The absorbing prepreg can be laid with a single brand for several layers, or with a combination of multiple brands, and even a wave-transmitting layer and a reflective layer can be added to prepare a stealth material, so as to meet the application requirements of diversified products.
[0029] 5. The production process of the absorbing prepreg of the present invention can be carried out step by step on different equipment, with flexible operation and relatively simple requirements on equipment functions. The components of the slurry formula and the resin formula can be flexibly adjusted within a certain range, so that a series of prepregs meeting different functional requirements can be produced according to actual needs, and the step-by-step production line equipment can be switched relatively quickly, thereby being able to meet the application needs of diversified products. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 Schematic diagram of the structure of the microwave absorbing prepreg with high carbon-based microwave absorbing agent content in Example 1; Figure 2 This is a schematic diagram of the structure of the three-dimensional fabric I-3 in Example 1; Figure 3 This is a schematic diagram of the three-dimensional fabric preparation process in Example 1; Figure 4 This is a schematic diagram of suturing in Example 1; Figure 5 This is a schematic diagram of the structure of the stealth composite material prepared using the absorbing prepreg with a high carbon-based absorber content in Experimental Example 1. DETAILED DESCRIPTION
[0031] The principles and features of the present invention are described below, and the examples are only used to explain the present invention and are not used to limit the scope of the present invention. If no specific conditions are specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially.
[0032] Example 1 A microwave absorbing prepreg with a high carbon-based microwave absorbing agent content, the structure of which is as follows Figure 1 As shown, the preparation method thereof comprises the following steps: (1) Reduced graphene oxide powder, butanone and aliphatic bifunctional epoxy resin GE-20 were mixed in a mass ratio of 50:45:5, stirred at 150 r / min for 40 min, and ground to a fineness of less than 20 μm to obtain glue solution I-1; wherein the reduced graphene oxide powder had an electrical conductivity of 8500 S / m, a particle size of 15 μm and a specific surface area of 240 m 2 / g; (2) The glue solution I-1 obtained in step (1) was heated to 970 g / m 2 Coated to a surface density of 60 g / m 2 On the glass fiber cloth, and then dried at 80℃ to form a film, to obtain fiber cloth Ⅰ-2; (3) Take two layers of fiber cloth I-2 obtained in step (2) and put them face to face (e.g. Figure 2 The two layers of fabric are then reinforced by sewing them together using an industrial sewing machine (as shown in Figure 3 and 4 As shown), nine sewing machine heads are arranged along the weft direction, with the needles spaced 10 cm apart in the weft direction, and they are stitched synchronously and continuously to obtain a three-dimensional fabric I-3; (4) Add reduced graphene oxide powder to epoxy resin, stir and mix at 500 r / min for 20 min, and grind to a fineness of less than 20 μm to obtain a mixed resin matrix II-1, wherein the reduced graphene oxide powder concentration is 1 wt%; the reduced graphene oxide powder has an electrical conductivity of 8500 S / m, a particle size of 15 μm, and a specific surface area of 240 m 2 / g; the epoxy resin system is E-51:GE-20:9506=40:13:46; (5) The mixed resin matrix II-1 obtained in step (4) was heated to 100 g / m 2 The mixture was evenly coated on the release paper, and then double-sidedly covered on the three-dimensional fabric I-3 obtained in step (3), and hot-pressed and impregnated at 60°C. The hot-pressing roller pressure was 0.3 MPa, the impregnation section drying tunnel length was 30 m, and the hot-pressing and impregnation time was 6 min, thereby obtaining an absorbing prepreg with a high carbon absorber content.
[0033] Example 2 A microwave absorbing prepreg with a high carbon-based microwave absorbing agent content, the preparation method of which comprises the following steps: (1) Reduced graphene oxide powder, carbon nanotubes, carbon black, ethyl acetate and active monomer diluent TTA-26 were mixed in a mass ratio of 40:10:5:40:5, stirred at 50 r / min for 50 min, and ground to a fineness of less than 20 μm to obtain gel solution I-1; (2) The glue solution I-1 obtained in step (1) was heated to 60 g / m 2 Coated on the glass fiber cloth surface, and then dried at 90°C to form a film to obtain fiber cloth Ⅰ-2; (3) Take two layers of fiber cloth I-2 obtained in step (2), put the sides coated with glue face to face, and then reinforce them by sewing technology to obtain three-dimensional cloth I-3; (4) Add reduced graphene oxide powder, carbon nanotubes and carbon black to epoxy resin, stir and mix at 400 r / min for 25 min, grind to a fineness of less than 20 μm, and obtain a mixed resin matrix II-1, wherein the specific component ratio is graphene: carbon nanotube: carbon black: E-44: TTA-26: DDA-10: U-415 = 0.8: 0.2: 0.1: 45: 33.7: 20: 0.2; (5) The mixed resin matrix II-1 obtained in step (4) was heated to 100 g / m 2 The mixture was evenly coated on the release paper, and then double-sidedly covered on the three-dimensional fabric I-3 obtained in step (3), and hot-pressed and impregnated at 70°C. The hot-pressing roller pressure was 0.3 MPa, the impregnation section drying tunnel length was 30 m, and the hot-pressing and impregnation time was 6 min, thereby obtaining an absorbing prepreg with a high carbon absorber content.
[0034] Example 3 A microwave absorbing prepreg with a high carbon-based microwave absorbing agent content, the preparation method of which comprises the following steps: (1) Reduced graphene oxide powder, butanone and GE-22 were mixed in a mass ratio of 30:60:10, stirred at 200 r / min for 30 min, and ground to a fineness of less than 20 μm to obtain glue solution I-1; wherein the reduced graphene oxide powder had an electrical conductivity of 8500 S / m, a particle size of 15 μm and a specific surface area of 240 m 2 / g; (2) The glue solution I-1 obtained in step (1) was heated to 350 g / m 2 Coated on the glass fiber cloth surface, and then dried at 80℃ to form a film to obtain fiber cloth Ⅰ-2; (3) Take two layers of fiber cloth I-2 obtained in step (2), put the sides coated with glue "face to face", and then sew and reinforce the two layers of cloth using an industrial sewing machine, with the needle spacing in the weft direction of 10 cm, and sew synchronously and continuously to obtain a three-dimensional cloth I-3; (4) Add reduced graphene oxide powder to epoxy resin and stir at 300 r / min for 30 min, grind to a fineness of less than 20 μm, and obtain a mixed resin matrix II-1, wherein the specific component ratio is reduced graphene oxide powder: E-51: GE-20: 9506 = 2:40:19:49; (5) The mixed resin matrix II-1 obtained in step (4) was heated to 200 g / m 2The mixture was evenly coated on the release paper, and then double-sidedly covered on the three-dimensional fabric I-3 obtained in step (3), and hot-pressed and impregnated at 60°C. The hot-pressing roller pressure was 0.3 MPa, the impregnation section drying tunnel length was 30 m, and the hot-pressing and impregnation time was 6 min, thereby obtaining an absorbing prepreg with a high carbon absorber content.
[0035] Example 4 A microwave absorbing prepreg with a high carbon-based microwave absorbing agent content, the preparation method of which comprises the following steps: (1) Reduced graphene oxide powder, butanone and GE-22 were mixed in a mass ratio of 40:50:10, stirred at 200 r / min for 30 min, and ground to a fineness of less than 20 μm to obtain glue solution I-1; wherein the reduced graphene oxide powder had an electrical conductivity of 8500 S / m, a particle size of 15 μm and a specific surface area of 240 m 2 / g; (2) The glue solution I-1 obtained in step (1) was heated to 350 g / m 2 Coated on the glass fiber cloth surface, and then dried at 80℃ to form a film to obtain fiber cloth Ⅰ-2; (3) Take two layers of fiber cloth I-2 obtained in step (2), put the sides coated with glue "face to face", and then sew and reinforce the two layers of cloth using an industrial sewing machine, with the needle spacing in the weft direction of 10 cm, and sew synchronously and continuously to obtain a three-dimensional cloth I-3; (4) Add reduced graphene oxide powder to epoxy resin and stir at 300 r / min for 30 min, grind to a fineness of less than 20 μm, and obtain a mixed resin matrix II-1, wherein the specific component ratio is reduced graphene oxide powder: E-51: GE-20: 9506 = 2.5: 40: 19: 49; (5) The mixed resin matrix II-1 obtained in step (4) was heated to 180 g / m 2 The mixture was evenly coated on the release paper, and then double-sidedly covered on the three-dimensional fabric I-3 obtained in step (3), and hot-pressed and impregnated at 60°C. The hot-pressing roller pressure was 0.3 MPa, the impregnation section drying tunnel length was 30 m, and the hot-pressing and impregnation time was 6 min, thereby obtaining an absorbing prepreg with a high carbon absorber content.
[0036] Example 5 A microwave absorbing prepreg with a high carbon-based microwave absorbing agent content, the preparation method of which comprises the following steps: (1) Reduced graphene oxide powder, butanone and GE-29 were mixed in a mass ratio of 50:45:5, stirred at 10 r / min for 20 min, and ground to a fineness of less than 20 μm to obtain glue solution I-1; wherein the reduced graphene oxide powder had an electrical conductivity of 8500 S / m, a particle size of 15 μm and a specific surface area of 240 m 2 / g; (2) The glue solution I-1 obtained in step (1) was heated to 1800 g / m 2 Coated on the surface of quartz fiber cloth, and then dried at 80°C to form a film, to obtain fiber cloth Ⅰ-2; (3) Take two layers of fiber cloth I-2 obtained in step (2), put the sides coated with glue "face to face", and then sew and reinforce the two layers of cloth using an industrial sewing machine. Nine sewing machine heads are arranged along the weft direction, with the needle heads spaced 10 cm apart in the weft direction, and sew synchronously and continuously to obtain a three-dimensional cloth I-3; (4) Add reduced graphene oxide powder to cyanate resin, stir and mix at 400 r / min for 20 min, grind to a fineness of less than 20 μm, and obtain a mixed resin matrix II-1, wherein the specific component ratio is reduced graphene oxide powder: cyanate resin: GE-29: DBTDL = 1:70:28.9:0.1; (5) The mixed resin matrix II-1 obtained in step (4) was heated to 200 g / m 2 The mixture was evenly coated on the release paper, and then double-sidedly covered on the three-dimensional fabric I-3 obtained in step (3), and hot-pressed and impregnated at 90°C. The hot-pressing roller pressure was 0.3 MPa, the impregnation section drying tunnel length was 30 m, and the hot-pressing and impregnation time was 6 min, thereby obtaining an absorbing prepreg with a high carbon absorber content.
[0037] Example 6 A microwave absorbing prepreg with a high carbon-based microwave absorbing agent content, the preparation method of which comprises the following steps: (1) Reduced graphene oxide powder, ethyl acetate and norbornyl acrylate (IBOA) were mixed in a mass ratio of 60:35:5, stirred at 100 r / min for 40 min, and ground to a fineness of less than 20 μm to obtain gel solution I-1; (2) The glue solution I-1 obtained in step (1) was heated to 1440 g / m 2 Coated on the surface of quartz fiber cloth, and then dried at 85℃ to form a film, to obtain fiber cloth Ⅰ-2; (3) Take two layers of fiber cloth I-2 obtained in step (2), put the sides coated with glue face to face, and then reinforce them by sewing technology to obtain three-dimensional cloth I-3; (4) Add reduced graphene oxide powder to acrylic resin, stir and mix at 350 r / min for 20 min, grind to a fineness of less than 20 μm, and obtain a mixed resin matrix II-1, wherein the specific component ratio is reduced graphene oxide powder: 6157B-80: IBOA: TMPTA: BPO = 2: 60: 32: 5: 1; (5) The mixed resin matrix II-1 obtained in step (4) was heated to 100 g / m 2The mixture was evenly coated on the release paper, and then double-sidedly covered on the three-dimensional fabric I-3 obtained in step (3), and hot-pressed and impregnated at 70°C. The hot-pressing roller pressure was 0.3 MPa, the impregnation section drying tunnel length was 30 m, and the hot-pressing and impregnation time was 6 min, thereby obtaining an absorbing prepreg with a high carbon absorber content.
[0038] Example 7 A microwave absorbing prepreg with a high carbon-based microwave absorbing agent content, the preparation method of which comprises the following steps: (1) Reduced graphene oxide powder, butanone and aliphatic bifunctional epoxy resin GE-20 were mixed in a mass ratio of 20:75:5, stirred at 10 r / min for 20 min, and ground to a fineness of less than 20 μm to obtain glue solution I-1; wherein the reduced graphene oxide powder had an electrical conductivity of 8500 S / m, a particle size of 15 μm and a specific surface area of 240 m 2 / g; (2) The glue solution I-1 obtained in step (1) was heated to 50 g / m 2 Coated on the glass fiber cloth surface, and then dried at 60°C to form a film to obtain fiber cloth Ⅰ-2; (3) Take two layers of fiber cloth I-2 obtained in step (2), put the sides coated with glue "face to face", and then sew and reinforce the two layers of cloth using an industrial sewing machine. Nine sewing machine heads are arranged along the weft direction, with the needle heads spaced 10 cm apart in the weft direction, and sew synchronously and continuously to obtain a three-dimensional cloth I-3; (4) Add reduced graphene oxide powder to epoxy resin, stir and mix at 50 r / min for 10 min, and grind to a fineness of less than 20 μm to obtain a mixed resin matrix II-1, wherein the concentration of reduced graphene oxide powder is 0.5 wt%; wherein the reduced graphene oxide powder has an electrical conductivity of 8500 S / m, a particle size of 15 μm, and a specific surface area of 240 m 2 / g, the epoxy resin system is E-51:GE-20:9506=40:13:46; (5) The mixed resin matrix II-1 obtained in step (4) was heated to 50 g / m 2 The mixture was evenly coated on the release paper, and then double-sidedly covered on the three-dimensional fabric I-3 obtained in step (3), and hot-pressed and impregnated at 50°C. The hot-pressing roller pressure was 0.3 MPa, the impregnation section drying tunnel length was 30 m, and the hot-pressing and impregnation time was 6 min, thereby obtaining an absorbing prepreg with a high carbon absorber content.
[0039] Example 8 A method for preparing a microwave absorbing prepreg with a high carbon-based microwave absorbing agent content comprises the following steps: (1) Reduced graphene oxide powder, carbon nanotubes, carbon black, ethyl acetate and active monomer diluent TTA-26 were mixed in a mass ratio of 30:10:10:40:10, stirred at 200 r / min for 40 min, and ground to a fineness of less than 20 μm to obtain gel solution I-1; (2) The glue solution I-1 obtained in step (1) was heated to 800 g / m 2 Coated on the glass fiber cloth surface, and then dried at 80℃ to form a film to obtain fiber cloth Ⅰ-2; (3) Take two layers of fiber cloth I-2 obtained in step (2), put the sides coated with glue face to face, and then reinforce them by sewing technology to obtain three-dimensional cloth I-3; (4) Add reduced graphene oxide powder, carbon nanotubes and carbon black to epoxy resin, stir and mix at 300 r / min for 20 min, grind to a fineness of less than 20 μm, and obtain a mixed resin matrix II-1, wherein the total concentration of reduced graphene oxide powder, carbon nanotubes and carbon black is 3 wt%, and the epoxy resin system is E-44:TTA-26:DDA-10:U-415=45:33.7:20:0.2; (5) The mixed resin matrix II-1 obtained in step (4) was heated to 800 g / m 2 The mixture was evenly coated on the release paper, and then double-sidedly covered on the three-dimensional fabric I-3 obtained in step (3), and hot-pressed and impregnated at 100°C. The hot-pressing roller pressure was 0.3 MPa, the impregnation section drying tunnel length was 30 m, and the hot-pressing and impregnation time was 6 min, thereby obtaining an absorbing prepreg with a high carbon absorber content.
[0040] Example 9 A method for preparing a microwave absorbing prepreg with a high carbon-based microwave absorbing agent content comprises the following steps: (1) Reduced graphene oxide powder, butanone and GE-20 were mixed in a mass ratio of 60:20:20, stirred at 500 r / min for 60 min, and ground to a fineness of less than 20 μm to obtain glue solution I-1; (2) The glue solution I-1 obtained in step (1) was heated to 3000 g / m 2 Coated on the glass fiber cloth surface, and then dried at 100°C to form a film to obtain fiber cloth Ⅰ-2; (3) Take two layers of fiber cloth I-2 obtained in step (2), put the sides coated with glue face to face, and then reinforce them by sewing technology to obtain three-dimensional cloth I-3; (4) Add reduced graphene oxide powder to epoxy resin, stir and mix at 1000 r / min for 30 min, and grind to a fineness of less than 20 μm to obtain a mixed resin matrix II-1, wherein the concentration of reduced graphene oxide powder is 5 wt%; (5) The mixed resin matrix II-1 obtained in step (4) was heated to 1000 g / m 2 The mixture is evenly coated on the release paper, and then covered on both sides of the three-dimensional fabric I-3 obtained in step (3), and hot-pressed and impregnated at 150°C to obtain an absorbing prepreg with a high carbon absorber content.
[0041] Comparative Example 1 A method for preparing a glue solution for a microwave absorbing prepreg comprises the following steps: (1) Mix reduced graphene oxide powder: butanone: GE-20 = 75:20:5 and stir at 25 °C and 100 r / min for 50 min.
[0042] Graphene has a large specific surface area. At this time, the amount of solvent and monomer diluent added is not enough to completely wet the graphene. There is a large amount of dry powder and the formula slurry cannot be completed.
[0043] Comparative Example 2 A composite fiber cloth with a single-sided enriched absorbent, the preparation method of which comprises the following steps (1) Reduced graphene oxide powder: butanone: GE-20 = 50:49:1 were mixed, stirred at 100 r / min for 40 min at 25 °C, and ground to a fineness of less than 20 μm to obtain glue solution I-1; (2) Use release paper as the backing and apply glue I-1 to the glass fiber cloth by single-sided coating. The coating amount is 980 g / m 2 The coating temperature is 40℃, the film is dried at 80℃, the drying tunnel length is 30m, the production speed is 3m / min, and a composite fiber cloth with single-sided enriched absorbent is obtained.
[0044] The composite fiber cloth enriched with absorbent on one side is rolled up in the reverse direction, with the absorbent enriched side facing outward. During the rolling process, a large amount of dried powder falls off, and the absorbent content cannot be guaranteed to reach the designed content; this indicates that the monomer diluent is too little and the absorbent cannot be effectively adhered; therefore, the subsequent preparation process cannot be carried out.
[0045] Test Example 1 The absorbing prepregs with high carbon absorber content prepared in Examples 1-6 were cut into sheets according to a size of 300 mm×300 mm, and 5 sheets of the cut prepregs were sequentially layered in a mold to reach a predetermined thickness. After the layering was completed, they were vacuum bagged, and a vacuum valve was assembled to prepare for tank curing. The step-by-step curing system with gradually increasing temperature and pressure (70°C / 3 bar / 1 h, 90°C / 5 bar / 2 h, and 110°C / 7 bar / 2 h, respectively) was used for hot pressing and curing to obtain a stealth composite material test sample (such as Figure 5 as shown).
[0046] The bow method of the national military standard GJB2038A-2011 was used to test the absorbing performance of the prepared stealth composite material. According to the test requirements, the composite material was trimmed into the size of the test sample and assembled on the device. The reflection loss was measured in the frequency range of 2-18 GHz to characterize the absorbing performance. The test results are shown in Table 1.
[0047] Table 1 Test results of the wave absorption performance of stealth composite materials
[0048] It can be seen from Table 1 that the stealth composite material test specimens prepared by the absorbing prepregs with high carbon-based absorber content in Examples 1-6 all have high absorbing efficiency.
[0049] Compared with carbonyl iron absorbers and other absorbers that significantly increase the weight of the material, carbon absorbers have the characteristics of low density, large specific surface area and strong oil absorption, and it is difficult to achieve high content addition in the resin formulation system. In this solution, after the glue is dried, the content of carbon absorbers can exceed 90 wt%, and the total carbon absorber content in the prepreg is 70 wt%, which not only improves the absorbing performance of the prepreg, but also helps to reduce the weight of the material.
[0050] Test Example 2 The effect of the preparation method was tested by using components in different proportions. The specific steps are as follows: (1) Reduced graphene oxide powder, butanone and GE-22 were mixed in different proportions as shown in Table 2, stirred at 100 r / min for 40 min, and ground to a fineness of less than 20 μm to obtain glue solution I-1; Table 2 Distribution ratio of each group in the glue solution
[0051] (2) The glue solution I-1 obtained in step (1) was successively heated to 960 g / m 2 , 450 g / m 2 , 235 g / m 2 , 340 g / m 2 and 110 g / m 2 Coated on the surface of quartz fiber cloth, and then dried at 80°C to form a film, to obtain fiber cloths 1-Ⅰ-2, 2-Ⅰ-2, 3-Ⅰ-2, 4-Ⅰ-2 and 5-Ⅰ-2; (3) Take two layers of fiber cloth Ⅰ-2 obtained in step (2) with the same number, put the sides coated with glue "face to face" together, and then sew and reinforce the two layers of cloth with an industrial sewing machine, with the needle spacing in the weft direction of 10 cm, and sew synchronously and continuously to obtain three-dimensional cloths 1-Ⅰ-3, 2-Ⅰ-3, 3-Ⅰ-3, 4-Ⅰ-3 and 5-Ⅰ-3; (4) Add reduced graphene oxide powder to epoxy resin in the proportions shown in Table 3, stir and mix at 300 r / min for 30 min, and grind to a fineness of less than 20 μm to obtain mixed resin matrices 1-Ⅱ-1, 2-Ⅱ-1, 3-Ⅱ-1, 4-Ⅱ-1 and 5-Ⅱ-1; Table 3 Distribution ratio of each component in the mixed resin matrix
[0052] (5) The mixed resin matrix II-1 obtained in step (4) was heated to 100 g / m 2 The mixture was evenly coated on the release paper, and then double-sidedly covered on the three-dimensional fabric I-3 obtained in step (3), and hot-pressed and impregnated at 60°C. The hot-pressing roller pressure was 0.3 MPa, the impregnation section drying tunnel length was 30 m, and the hot-pressing and impregnation time was 6 min, thereby obtaining an absorbing prepreg with a high carbon absorber content.
[0053] It can be seen that the resin system, absorber, fiber cloth, the proportion and type of each component in the prepreg, as well as the total amount of absorber added can all be adjusted according to actual application requirements.
[0054] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a microwave absorbing prepreg having a high carbon-based microwave absorbing agent content, characterized in that: The following steps are involved: (1) stirring and mixing a carbon absorber, a volatile solvent and an active monomer diluent, and grinding and dispersing them to obtain a glue solution I-1; (2) coating the adhesive solution I-1 obtained in step (1) onto the surface of the fiber cloth, and then drying it to form a film to obtain the fiber cloth I-2; (3) Take two layers of fiber cloth I-2 obtained in step (2), put the sides coated with glue face to face, and then reinforce them by sewing technology to obtain three-dimensional cloth I-3; (4) adding the carbon-based absorber to the resin matrix, stirring, mixing, grinding and dispersing, and obtaining a mixed resin matrix II-1; (5) The mixed resin matrix II-1 obtained in step (4) is impregnated into the three-dimensional fabric I-3 obtained in step (3) by hot melt impregnation to obtain an absorbing prepreg with a high carbon absorber content.
2. The method for preparing a microwave absorbing prepreg having a high carbon-based microwave absorbing agent content according to claim 1, characterized in that: In steps (1) and (4), the carbon-based absorber is at least one of graphene, carbon nanotubes, carbon black and silicon carbide.
3. The method for preparing a microwave absorbing prepreg having a high carbon-based microwave absorbing agent content according to claim 1, characterized in that: In steps (1) and (4), the powder is ground to a fineness of less than 20 μm.
4. The method for preparing a microwave absorbing prepreg having a high carbon-based microwave absorbing agent content according to claim 1, characterized in that: In step (1), the concentration of the carbon absorber in the glue solution I-1 is 20-60 wt%, and the concentration of the active monomer diluent is 5-20 wt%.
5. The method for preparing a microwave absorbing prepreg having a high carbon-based microwave absorbing agent content according to claim 1, characterized in that: In step (2), the coating amount of the adhesive solution I-1 is 50-3000 g / m 2 .
6. The method for preparing a microwave absorbing prepreg having a high carbon-based microwave absorbing agent content according to claim 1, characterized in that: In step (2), the drying temperature is 60-100°C.
7. The method for preparing a microwave absorbing prepreg having a high carbon-based microwave absorbing agent content according to claim 1, characterized in that: In step (4), the concentration of the carbon-based absorber in the mixed resin matrix II-1 is 0.5-5 wt%.
8. The method for preparing a microwave absorbing prepreg having a high carbon-based microwave absorbing agent content according to claim 1, characterized in that: In step (4), the resin matrix is one of epoxy resin, cyanate resin and acrylate resin.
9. The method for preparing a microwave absorbing prepreg having a high carbon-based microwave absorbing agent content according to claim 1, characterized in that: In step (5), the hot melt impregnation method comprises the following steps: mixing the mixed resin matrix II-1 obtained in step (4) at a temperature of 50-1000 g / m 2 The mixture is evenly coated on the release paper and then covered with the three-dimensional fabric I-3 obtained in step (3). The mixture is hot-pressed and impregnated at 50-150°C to obtain an absorbing prepreg with a high carbon absorber content.
10. The microwave absorbing prepreg with high carbon-based microwave absorbing agent content obtained by the method for preparing the microwave absorbing prepreg with high carbon-based microwave absorbing agent content according to any one of claims 1 to 9.
Citation Information
Patent Citations
Composite wave-absorbing material and preparation method thereof
CN112208183A
Wave-absorbing material and preparation method thereof
CN114132014A
RADAR-ABSORBING MULTILAYER LAMINATE FOR AIRCRAFT MADE OF POLYMER MATRIX COMPOSITE MATERIAL WITH GRAPHENE NANOPLATES
IT201800003182A1
A roll-type composite sheet with enhanced electromagnetic wave-shielding and -absorbing, and heat-releasing properties, and a method for preparation of the same
KR100874690B1
Composite material and electromagnetic wave absorber molded from same
WO2021157309A1